Unified Algebras and Abstract Syntax - Mosses, Peter D. (BRICS Report Series, 1994)
We consider the algebraic specification of abstract syntax in the framework of unified algebras. We illustrate the expressiveness of unified algebraic specifications, and provide a grammar-like notation for specifying abstract syntax, particularly attractive for use in semantic descriptions of full-scale programming languages.